Selective construction of dispiro[indoline-3,2'-quinoline-3',3''-indoline] and dispiro[indoline-3,2'-pyrrole-3',3''-indoline] via three-component reaction - Xiao, Ziying; Xu, Fengshun; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2023)
A convenient synthetic procedure for the construction of novel dispirooxindole motifs was successfully developed by base-promoted three-component reaction of ammonium acetate, isatins and in situ-generated 3-isatyl-1,4-dicarbonyl compounds. The piperidine-promoted three-component reaction of ammonium acetate, isatins and the in situ-generated dimedone adducts of 3-ethoxycarbonylmethyleneoxindoles afforded mutlifunctionalized dispiro[indoline-3,2'-quinoline-3',3''-indoline] derivatives in good yields and with high diastereoselectivity. On the other hand, a similar reaction of the dimedone adducts of 3-phenacylideneoxindoles afforded unique dispiro[indoline-3,2'-pyrrole-3',3''-indoline] derivatives with a cyclohexanedione substituent. A plausible reaction mechanism is proposed to explain the formation of the different spirooxindoles.
Keywords: cascade reaction; dimedone; isatin; 3-methyleneoxindole; multicomponent reaction; spirooxindole